THE ROLE OF FINTECH IN IMPROVING ISLAMIC FINANCIAL INCLUSION IN THE ERA OF FINANCIAL DIGITALIZATION - ramadhan, Muh.fitra (Sipakainge: Inovasi Penelitian, Karya Ilmiah, dan Pengembangan (Islamic Science), 2025)
This article aims to analyze the contribution of fintech in promoting Islamic financial inclusion in the digitalization era through a Systematic Literature Review (SLR) approach. By reviewing 30 relevant scholarly articles from 2016 to 2024, this study maps the role of fintech in expanding access to Sharia-based financial services, particularly for vulnerable groups such as MSMEs, Islamic boarding schools (pesantren), and rural communities. The literature search strategy employed thematic keywords and Boolean operators, while the article selection process followed PRISMA and CASP guidelines to ensure the validity of the findings. The results indicate that fintech holds significant potential in bridging the gap in access to Islamic finance through the digitalization of services, although challenges such as regulatory limitations, digital literacy, and infrastructure remain major obstacles. Practically, this article recommends the need for synergy among industry players, regulators, and Islamic financial institutions in creating an inclusive digital ecosystem that aligns with Sharia principles. Theoretically, this study enriches the understanding of the integration between fintech, digitalization, and financial inclusion within the framework of modern Islamic economics.